Pengelolaan Wisata Pantai Nambo dalam Meningkatkan Pendapatan Asli Daerah Kota Kendari di Massa Pandemi Covid 19 - Erlin, Erlin; Ihsan Mattalitti, Muhammad; Awaluddin Ma’ruf, Andi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Kendari, 2021)
This study describes how the management of Nambo beach by the Kendari City Culture and Tourism Office to increase regional revenue during the Covid-19 emergency response. Through a qualitative approach, data collection activities are carried out through observation, interviews, document study. The informants in this study were 12 people consisting of the Head of the Service, the Head of the Destination Division, the Head of the Tourism Attraction Section, the Head of the Planning Subdivision, the Beach Manager and the Tourism Awareness Group. The findings of this study indicate that the Nambo beach management process in the aspects of planning the determination of targets and formulation of strategies has been well arranged. Even though the target achievement has not been met due to the decline in the number of visitors to Nambo beach during the Covid 19 pandemic. Furthermore, the organization in terms of the number of staff and the division of duties has not been effective because of the excessive number of staff and also no division of work areas such as the division of staff work areas. encouraging employee workmotivation has been effective because the provision of smooth incentives can increase employee morale. Control in terms of comparison between plans and realization has not been effective. Where, in addition to the obligatory factor of levies who are not aware of the importance of paying fees, there is also poor management of traders because they do not know the number of active traders